2016
DOI: 10.1038/srep25069
|View full text |Cite
|
Sign up to set email alerts
|

Screening of efficient siRNA carriers in a library of surface-engineered dendrimers

Abstract: Polymers are widely used as non-viral carriers for siRNA delivery, but concern has also arisen in their limited efficacy and inherent toxicity. Whilst many of previous efforts have been documented towards improving the performance of polymers via chemical modifications, the structure-activity relationships (SAR) of these ligand-modified polymers are not well understood. To address this issue, we systemically prepared a library of surface-engineered dendrimers (>300) as the screening pool to discover efficient … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 54 publications
1
25
0
Order By: Relevance
“…The end group can be functionalized; providing a variety of functions. On the surface of the polymer, significantly positive amine functional groups are also found, which are conducive for tight binding with siRNA (Liu et al, 2016). Recently, cationic dendrimers have been studied as carriers for siRNA delivery.…”
Section: Dendritic Polymermentioning
confidence: 99%
See 1 more Smart Citation
“…The end group can be functionalized; providing a variety of functions. On the surface of the polymer, significantly positive amine functional groups are also found, which are conducive for tight binding with siRNA (Liu et al, 2016). Recently, cationic dendrimers have been studied as carriers for siRNA delivery.…”
Section: Dendritic Polymermentioning
confidence: 99%
“…Genasense can specifically bind to human Bcl-2 mRNA, which leads to the catalytic degradation of Bcl-2 mRNA and reduces the translation of Bcl-2 protein. Therefore, researchers can use mRNA degradation strategies and small inhibitory molecules for targeted Bcl-2 therapy in a variety of cancers, such as breast cancer, colon cancer, and prostate cancer ( Li et al, 2016 ). Moreover, preclinical studies have shown that the combination of Bcl-2 antisense and chemotherapy improved the anti-tumour response, thereby increasing the apoptosis of tumor cells and improving the survival rate.…”
Section: Launched and Ongoing Drugsmentioning
confidence: 99%
“…Dendrimers have positively charged amine functionalities at the surface that enable condensation of negatively charged siRNA molecules through electrostatic interactions. They also have tertiary amine groups in the interior that can be protonated in acidic endosomes to initiate the proton sponge effect (Liu et al 2016). The most common de ndrimer use d for siRNA delive ry systems is poly(amidoamine) (PAMAM) (Gu et al 2015;Sun et al 2017b), a cationic polymer that has good pH buffering capability.…”
Section: Nanoparticlesmentioning
confidence: 99%
“…Liu and colleagues [ 102 ] published a library of surface-engineered dendrimers, which can be applied as siRNA carriers. Structure–activity relationship (SAR) studies demonstrated that hydrophobic ligands—such as aliphatic chains, aromatic rings, fluorine, and bromine atoms—are fundamental for polymers, since they may provide high levels of gene silencing efficacy.…”
Section: Biomedical Applicationsmentioning
confidence: 99%